2020
DOI: 10.1002/eji.202048556
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota disruption limits the isoniazid mediated clearance of Mycobacterium tuberculosis in mice

Abstract: Tuberculosis (TB) continues to remain a global threat due to the emergence of drugresistant Mycobacterium tuberculosis (Mtb) strains and toxicity associated with TB drugs. Intestinal microbiota has been reported to affect the host response to immunotherapy and drugs. However, how it affects the potency of first-line TB drug isoniazid (INH) is largely unknown. Here, we examined the impact of gut microbial dysbiosis on INH efficiency to kill Mtb. In this study, we employed in vivo mouse model, pretreated with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…It has been demonstrated that in mice, disruption of the gut microbiota promotes susceptibility to Mycobacteria tuberculosis (MTB) infection ( 7 ). Furthermore, disruption of the gut microbiota also impairs the isoniazid (INH)-mediated MTB clearance by suppressing the innate immunity and reducing the CD4 T-cell response to MTB ( 8 ). It was found that the gut bacterial microbiome changed in the active TB patients compared with healthy subjects ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in mice, disruption of the gut microbiota promotes susceptibility to Mycobacteria tuberculosis (MTB) infection ( 7 ). Furthermore, disruption of the gut microbiota also impairs the isoniazid (INH)-mediated MTB clearance by suppressing the innate immunity and reducing the CD4 T-cell response to MTB ( 8 ). It was found that the gut bacterial microbiome changed in the active TB patients compared with healthy subjects ( 9 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, after 1 week of TB treatment, OTU8 and OTU2972 assigned to the family Erysipelotrichaceae strikingly increased, whereas the rest of the Erysipelotrichaceae family declined. Similarly, Negi, Pahari (18) applied an in vivo mouse model and found that broad-spectrum antibiotics could lead to significant alterations in gut microbiota composition with decreased abundance of commensal bacteria Campylobacter, Bifidobacterium, and Lactobacillus, and increased abundance of Enterococcus and Bacteroides. Multiple antibiotics in the case of TB treatment could not only result in immediate dramatic changes in gut microbiota composition but also even after a long period of recovery.…”
Section: Effects Of Anti-tb Treatment On Gut Microbiotamentioning
confidence: 99%
“…18) applied an in vivo mouse model to study the influence of gut microbiota dysbiosis on isoniazid (INH) efficiency against M. tuberculosis, and found that a declined abundance of Lactobacillus, Bifidobacterium, and Campylobacter caused by antibiotic pre-treatment could lead to immune response impairment to INH treatment in M. tuberculosis clearance and more serious granulomatous development. In addition, this group also demonstrated that impairment of the intestinal innate defense and immunity stemmed from microbiota changes during INH therapy, and resulted in lower levels of antimicrobial peptide RegIII γ and pro-inflammatory cytokines TNF-α and IFN-γ, and higher levels of anti-inflammatory cytokine IL-10.…”
mentioning
confidence: 99%
“…A recent study on the effects of intestinal microbiome on INH efficacy using mice model showed changes into the gut microbiome population and the abolishment of innate immune response against MTB during INH therapy by a downregulation in the expression of MHC-II and CD86 which diminished the antigen presentation ability and activation of myeloid DCs in lung. Moreover a reduction of the expression of innate receptors ( TLR2 , Mincle and Nod2 ) caused by microbiota disruption was observed in MTB infected mice under INH therapy ( Negi et al., 2020 ). Those findings raise the possibility that the composition of the microbiota may influence treatment outcome and future resistance against the disease.…”
Section: Impact Of Antituberculosis Treatment On the Gut Microbiomementioning
confidence: 99%
“…An in vivo mouse model to study the influence of gut microbiota dysbiosis on isoniazid (INH) efficiency against M. tuberculosis , was conducted by Liu et al and they found that a declined abundance of Lactobacillus, Bifidobacterium , and Campylobacter caused by antibiotic pre-treatment is susceptible impairing the immune response to isoniazid treatment in M. tuberculosis clearance. Moreover the impairment of the intestinal innate defense and immunity stemmed from microbiota changes during INH therapy ( Negi et al., 2020 ; Liu et al., 2021 ). More detailed studies are required to better understand the gut microbiota-anti-TB drugs interaction.…”
Section: Pharmacomicrobiomicsmentioning
confidence: 99%